Աղբերց վանք -Գլաձորի մասին պատմական եւ տեղագրական վկայութիւնների քննութիւն - Մաթեւոսեան, Կարէն (տպ. Atlas)
Gladzor University, which functioned in the Aghberts monastery of Vayots Dzor province between 1282 and 1338, is one of the exceptional institutions of the educational, scientific and cultural life of medieval Armenia. Unfortunately, its exact location is still unknown. The history and activities of this center have been studied to a sufficient extent, but so far there has not been a complete, comprehensive presentation of the historical and topographical data available in the primary sources about it. This article is an endeavor in that direction. The research enables us to clearly see in which years and by what names the monastery is mentioned: Aghberts monastery or Gladzor (or both together), which churches and sanctuaries are mentioned, what additional names are given to the monastery and the university, etc. The table presented in this article is a compilation of excerpts from all 33 available manuscripts which have referred to the said institution. After analyzing these data, the author concludes that these materials prove that Gladzor was located in the basin of the Yeghegis River, in a high place where there were springs. Furthermore, the information gathered enables us to infer that both Gladzor and the Hermon monastery of Vayots Dzor province had close relations, and in 1338 the university moved to Hermon. In conclusion the author argues that Gladzor was located not far from Hermon monastery.
Keywords: Հայոց պատմութիւն; Աղբերց վանք; Գլաձոր